Floral and Yield Attributes of Tuberose as Influenced by Gibberellic Acid - Amin, Md. Ruhul; Sultana, Salma; Hossain, Md. Ismail; Sarkar, Md. Dulal (International Journal of Bio-resource and Stress Management, 2017)
The present work was studied to modify the floral and yield contributing characters of tuberose by the influence of gibberellic acid. During the experiment four treatments were tested: control, 100 ppm, 200 ppm and 300 ppm with three replications. The experiment was conducted over two growing periods during April 2013 to March 2015 at Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh. Gibberellic acid regulated the development of spike, bulb and bulblet. GA3 @ 200 ppm was more effectiveon floral initiation, floret iflorescence-1, bulb and bulblet production compared to control. Maximum flowering plants about 92.56%, bulb yield about 15.86 t ha-1 and bulblet yield about 13.60 t ha-1 were found from the plants treated with GA3 @ 200 ppm. Therefore, GA3 @ 200 ppm were found to be effective for the tuberose production rather than other treatments.